Ten years of oxygen and hydrogen isotopic composition of daily precipitation at Concordia station, East Antarctica - DREOSSI G; STENNI B; MASIOL M; POSOCCO V (INGV Istituto Nazionale di Geofisica e Vulcanologia, 2022)
Here we present a 10year (20082017) record of the isotopic composition of precipitation at Dome C. The winterover personnel at Concordia Station have been continuously collecting daily precipitation since 2008: this represents a unique record of the isotopic composition of precipitation from the Antarctic Plateau. Snow is collected on a raised platform (height: 1 m) in the clean area of the station and analyzed for d18O, dD and deuterium excess. A significant positive correlation between d18O (dD) of precipitation and 2m air temperature is observed at different temporal scale; the lowest temperature and isotopic values are preferentially observed during winters affected by a strongly positive Southern Annular Mode index [Stenni et al., 2016]. We have compared the isotopic data of Concordia samples with meteorological data from the Dome C AWS of the Programma Nazionale di Ricerche in Antartide (PNRA), as well as with the isotopeenabled atmospheric general circulation models ECHAM5wiso and ECHAM6wiso, in order to improve the understanding of the mechanisms governing the isotopic composition of precipitation on the Antarctic plateau, which are yet to be fully understood, as well as the postdepositional effects altering the pristine isotopic signal of precipitation. The comprehension of these physical processes is fundamental for reconstructing past temperature variations using the isotopic records from ice cores drilled in low accumulation areas of Antarctica [Casado et al., 2018], e.g., the upcoming Beyond EPICA drilling at Little Dome C. Very few temporal relationships between temperature and snow isotopic composition, mostly limited in time or sampling frequency, have been calculated, while spatial relationships have been traditionally used to reconstruct past temperature from ice core isotopic records [MassonDelmotte et al., 2008].